KRISTAL CAIR LAMELAR DALAM SISTEM AIR, TETRA ETILEN GLIKOL DODESIL ETER, DAN TEMBAGA NITRAT - Ali Amran (Universitas Andalas, 2010)
JRK Vol. 3, No. 2ABSTRACT The lamellar liquid crystal in water, tetraethyleneglycol dodecylether, and copper nitrate system has been investigated. The results which characterized using optical polarizing microscope and small-angle x-ray diffraction showed the stability of the liquid crystal region was 40% and 65% by weight of surfactant. The interlayer spacing of lamellar liquid crystal, with and without various concentrations of copper nitrate content, remained constant. Keywords : Lamellar liquid crystal, Tetraethylene glycol dodecylether, Copper nitrate, Optical polarizing microscope, Small-angle x ray diffraction